Interaction of Butterfly (Lepidoptera: Papillionoidea) and Flowering Plants in The Forest Area of The Cibubur Arboretum Jakarta - Hasni Ruslan Dwi Andayaningsih Farhana Auliadin (Journal of Tropical Biodiversity, 2022)
Butterfly observation research in the Arboretum City Forest area has been widely known, but research related to interaction of butterflies and flowering plants is still scarce. The Aim of this study was to determined the interaction of butterflies and flowering plants in the Cibubur Arboretum City Forest area. We found 45 species, 4 families with 232 individuals, which consists of four butterfly families, includingPapilionidae, Pieridae, Nymphalidae, and Lycenidae. The results of this study are different from the results ofresearch conducted in 2014. We found that the number of individuals and species are decreased. Based on the diversity index value in 2014, and current situation,has a similar moderate category diversity index. This can be due to the presence of the same feed plants and host plants in this area. Several types of flowering plants were found at the research site: Asystasiagangetica, Emilia sanchofolia, Synedrella sp., Kyllingasp., and Mimosa pudica. There are some of the same plants found in both opened and closed habitats such asPolyalthialongifolia, Diffenbachiaseguine, Cecropianpeltata, Parkiaspeciosa , and Swieteniamahagoni. The butterfly species Leptosianina is one of the species found in high numbers in the Arboretum City Forest area, due to the many host plants found in this area. The correlation analysis showed a strong relationship between flowering plants and the number of individual butterflies in both habitats (opened and closed). The Asystasyagangetica plant is widely used by butterflies as a food source